2008
DOI: 10.1007/s00168-008-0257-4
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution of inventor networks

Abstract: O31, N34, R11,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(77 reference statements)
0
11
0
1
Order By: Relevance
“…Assuming that actors choose cooperation partners according to their abilities, actors included in a network have been positively evaluated. This positive selection of relatively able cooperation partners should have a positive effect on the probability of success (Granovetter 1995;Storper & Venables 2004;Wilhelmsson 2009). Venables 2004).…”
Section: Division Of Innovative Labor Innovation Network and Regiomentioning
confidence: 99%
“…Assuming that actors choose cooperation partners according to their abilities, actors included in a network have been positively evaluated. This positive selection of relatively able cooperation partners should have a positive effect on the probability of success (Granovetter 1995;Storper & Venables 2004;Wilhelmsson 2009). Venables 2004).…”
Section: Division Of Innovative Labor Innovation Network and Regiomentioning
confidence: 99%
“…Tacit information and knowledge flows are concentrated in space because personal learning and sharing rely heavily on face-to-face interaction [55,56]. However, information exchanges also occur in long-distance and wide-ranging networks of collaboration through formal and informal relationships [6][7][8][9][10]. Creative firms build and sustain external and internal resources that can develop resilience capacity to minimize the effects of disasters and reduce economic losses [30,33,35].…”
Section: Discussionmentioning
confidence: 99%
“…Innovation processes within geographical clusters, tied to localized knowledge flows, have been extensively documented and are widespread across the U.S. and Europe [1][2][3][4][5]. While these empirical studies are remarkable in their geography scheme, information exchange develops in wide-ranging and long-distance networks of collaboration through formal and informal relationships [6][7][8][9][10][11][12]. Breschi and Lissoni [13] pointed out that knowledge exchange is not restricted to local networking in clusters only, but can also be distributed to distant areas via a variety of interactions [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…In an article that investigates innovation at the same geographic scale, Wilhemsson (2008) draws upon evidence of 2,000 interfirm patent holders in 100 Swedish labor markets. His study seeks to determine whether the infrequent collaborative networks observed represent efforts by firms in 16 core technologies to compensate for local deficits of proximity and agglomerative externalities.…”
Section: Synthesis In Progressmentioning
confidence: 99%